Native Production of Prodigiosin in the Estuarine Bacterium, Vibrio gazogenes PB1, and Identification of the Associated pig Genes - Vijay, Dhanya; Baby, Bincy; Alhayer, Maryam S.; Vijayan, Ranjit; Akhtar, M. Kalim (Frontiers in Marine Science, 2022)
Vibrio gazogenes PB1 is an estuarine bacterium that was first isolated from saltwater mud. This bacterial species possesses the metabolic capacity to produce prodigiosin which has potential uses as an anticancer agent, antibiotic, and a fungicide. We evaluated the feasibility of employing V. gazogenes PB1 as a bacterial host for the production of prodigiosin. V. gazogenes PB1 could be grown and maintained using the well-known lysogeny broth medium when supplemented with NaCl, and revived after storage at -80°C. Under batch conditions, growth of V. gazogenes PB1 in minimal media and production of prodigiosin was observed over a wide range of NaCl concentrations from 1 to 5% (w/v). The production of prodigiosin was significantly influenced by the concentration of glucose (as the carbon source), ammonium chloride (as the nitrogen source), inorganic phosphate ions, as well as pH. The greatest titer (231 mg/L) was observed in minimal media that contained 1% (w/v) glucose, 100 mM ammonium chloride and 100 mM potassium phosphate buffer. The sequences and chromosomal locations of the pig genes associated with prodigiosin biosynthesis are revealed for the first time. PigA is an isolated gene on chromosome 2, while the remaining pig genes, from pigB to pigN, exist as a 20 kb gene cluster on chromosome 1. Given its excellent growth in a range of NaCl concentrations, wide availability from culture collections and low-risk status for experimental work, we would conclude that V. gazogenes PB1 is a promising bacterial host for the production of prodigiosin.